TEACHER COMMUNICATION STRATEGIES IN TEACHING STUDENT'S INTELLECTUAL DISABILITY - Lenie Okviana; Budi Santosa; Sendi Eka Nanda (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The phenomenon of the teaching and learning process of students with intellectual disabilities is quite interesting, because of the development of a child who shows limitations in intellectual functioning and social adaptation. Students with intellectual disabilities have below-average intelligence and difficulty learning, understanding, and solving problems, especially in communication. The purpose of this study is to find out how the communication strategies used by teachers in teaching students with intellectual disabilities at the elementary, junior high, and high school levels at the SLB B / C Budi Lestari Education Foundation, Sukatani Depok. This research uses Charles Berger's theory of Planning and the theory of Symbolic Interactionism by George Herbert Mead. This research uses qualitative methods and constructivist paradigms. The results of this study show that teacher communication strategies in teaching students with intellectual disabilities both elementary, junior high, and high school at the SLB B / C Budi Lestari Sukatani Education Foundation, Depok are using media assistance and combining verbal and non-verbal forms of communication in the learning process. Teachers apply communication strategies, namely to secure understanding, to establish acceptance, and to motivate action. The process of implementing strategies is carried out by interacting using the help of media such as images, computers, body language, and facial expressions.